MANAJEMEN SARANA DAN PRASARANA SEKOLAH - Nurbaiti Nurbaiti (UNIVERSITAS BENGKULU, 2015)
The purpose of this study was to describe the management of facilities and infrastructure in the Primary School 02 East Curup. Methods this study uses a qualitative descriptive study. Subjects in this study were the principal and teacher. The conclusions of this study indicate the facilities and infrastructure planning and procurement conducted by the principal in accordance with the provisions, an inventory of school facilities and infrastructure has been done well, distribution is done directly and indirectly, maintenance of school facilities and infrastructure is done by periodically and incidental, control and accountability (reporting)infrastructure carried out by the principal and done once a year when the new school year. general management of facilities and infrastructure already implemented.Keyword: management, facilities, infrastructure